Iowa RBA, December 15, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for December 15, 1997. Highlights of the update include two outstanding birds, a second state record Ross's Gull and Clark's Grebe. Other sightings of note include a Black-legged Kittiwake, a Varied Thrush, a Western Grebe, and White-winged Crossbills. Also included are handwritten notes for the next week's update with sightings of a Prairie Falcon and Short-eared Owls. Epson - sheet feed/flatbed